Financial cost analysis of a strategy to improve the quality of administrative vaccination data in Uganda. Issue 5 (29th January 2020) - Ward, Kirsten; Mugenyi, Kevin; MacNeil, Adam; Luzze, Henry; Kyozira, Carol; Kisakye, Annet; Matseketse, David; Newall, Anthony T.; Heywood, Anita E.; Bloland, Peter; Pallas, Sarah W.
Highlights: Little evidence of cost to improve vaccination data quality in low-resource settings. Uganda implemented a 2-year national strategy to improve vaccination data quality. Strategy financial cost was US 4030 per district and US 136 per health facility in 2016. Operational costs were 0.5–1.6% of Uganda's national immunization program costs. Abstract: Background: High-quality vaccination data are critical to planning, implementation and evaluation of immunization programs. However, sub-optimal administrative vaccination data quality in low- and middle-income countries persist for heterogeneous reasons, though most relate to organizational factors and human behavior. The nationwide Data Improvement Team (DIT) strategy in Uganda aimed to strengthen human resource capacity to generate quality administrative vaccination data at the health facility. Methods: A financial cost analysis of the Uganda DIT strategy (2014–2016) was conducted from the program funder perspective. Activity-based micro-costing from funder financial and program monitoring records was used to estimate total and unit costs by program area (in 2016 US dollars). Hypothetical scenarios were developed to illustrate potential approaches to reducing costs. Results: Over 25 months the DIT strategy was implemented in all 116 operational districts and 3443 (89%) health facilities in Uganda at a total financial cost of US 575 275. Training and deployment of DITs accounted for the highest proportion of expenditure across program areas (69%). Transport, per diems, lodging, and honoraria for DIT members and national supervisors were the main cost drivers of the strategy. Deployment of 557 DIT members cost US 839 per DIT member, US 4 030 per district, and US 136 per health facility. The estimated opportunity cost of government staff time wasn't a major cost driver (2.5%) of total cost. Conclusion: The results provide the first estimates of the magnitude and drivers of cost to implement a national workforce capacity building strategy to improve administrative vaccination data quality in a low- or middle-income country. Financial costs are a critical input to combine with future outcome data to describe the cost of strategies relative to performance outcomes. The operational costs of the strategy were modest (0.5–1.6%) relative to the estimated operational costs of Uganda's national immunization program.